Further expansions:
H(ε_0^(ω+1)(ω+1)+ε_0^(ω+1),2)
= H(ε_0^(ω+1)(ω+1)+(ε_0^ω)ε_0,2)
= H(ε_0^(ω+1)(ω+1)+(ε_0^ω)(ω^ω),2)
= H(ε_0^(ω+1)(ω+1)+(ε_0^ω)(ω^2),2)
= H(ε_0^(ω+1)(ω+1)+(ε_0^ω)(ω2),2)
= H(ε_0^(ω+1)(ω+1)+(ε_0^ω)(ω+2),2)
= H(ε_0^(ω+1)(ω+1)+(ε_0^ω)(ω+1)+ε_0^2,2)
= H(ε_0^(ω+1)(ω+1)+(ε_0^ω)(ω+1)+(ε_0)(ω^ω),2)
= H(ε_0^(ω+1)(ω+1)+(ε_0^ω)(ω+1)+(ε_0)(ω^2),2)
= H(ε_0^(ω+1)(ω+1)+(ε_0^ω)(ω+1)+(ε_0)(ω2),2)
= H(ε_0^(ω+1)(ω+1)+(ε_0^ω)(ω+1)+(ε_0)(ω+2),2)
= H(ε_0^(ω+1)(ω+1)+(ε_0^ω)(ω+1)+(ε_0)(ω+1)+ω^ω,2)
= ...
H(ε_0^(ω+1)(ω+1)+ε_0^(ω+1),2)
= H(ε_0^(ω+1)(ω+1)+(ε_0^ω)ε_0,2)
= H(ε_0^(ω+1)(ω+1)+(ε_0^ω)(ω^ω),2)
= H(ε_0^(ω+1)(ω+1)+(ε_0^ω)(ω^2),2)
= H(ε_0^(ω+1)(ω+1)+(ε_0^ω)(ω2),2)
= H(ε_0^(ω+1)(ω+1)+(ε_0^ω)(ω+2),2)
= H(ε_0^(ω+1)(ω+1)+(ε_0^ω)(ω+1)+ε_0^2,2)
= H(ε_0^(ω+1)(ω+1)+(ε_0^ω)(ω+1)+(ε_0)(ω^ω),2)
= H(ε_0^(ω+1)(ω+1)+(ε_0^ω)(ω+1)+(ε_0)(ω^2),2)
= H(ε_0^(ω+1)(ω+1)+(ε_0^ω)(ω+1)+(ε_0)(ω2),2)
= H(ε_0^(ω+1)(ω+1)+(ε_0^ω)(ω+1)+(ε_0)(ω+2),2)
= H(ε_0^(ω+1)(ω+1)+(ε_0^ω)(ω+1)+(ε_0)(ω+1)+ω^ω,2)
= ...